2013
DOI: 10.1111/jpc.12416
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of children with learning and behavioural problems: Comparison of a multidisciplinary and sole paediatrician model

Abstract: Parents attending both clinics were satisfied with the assessment process. MD assessment of children with suspected learning and/or behavioural concerns appears to have the additional benefit of helping families to better understand their child's difficulties. Fewer families attending MD clinics reported that recommendations were useful and practical compared with the SP model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…There is also the risk of assessment findings not being optimally linked to delivery of care and intervention . Emerging evidence supports the importance of service structure emphasising links between multidisciplinary assessments and secondary care, with parents valuing information regarding their child's strengths and weakness gained from multidisciplinary assessments, but finding recommendations from sole paediatricians more useful …”
Section: Discussionmentioning
confidence: 99%
“…There is also the risk of assessment findings not being optimally linked to delivery of care and intervention . Emerging evidence supports the importance of service structure emphasising links between multidisciplinary assessments and secondary care, with parents valuing information regarding their child's strengths and weakness gained from multidisciplinary assessments, but finding recommendations from sole paediatricians more useful …”
Section: Discussionmentioning
confidence: 99%
“…88 Multiple parent-reported measures of child behavior were included in 13 studies. In 4 of these studies, 45,46,55,56,72 a difference in child behavior was observed between groups for some measures and not others, and these findings were unexplained by the theory of the intervention's mechanism. For example, Patterson et al 56 found that ECBI Intensity scores improved more in the intervention than control group at 6-month follow-up.…”
Section: Outcomes Measuredmentioning
confidence: 97%